Al-Idārāh al-Istirātījiyyah fī Ta’līm al-Lugah al-‘Arabiyyah bi al-Ma’had - Budiman, Agus; Wibowo, Safrudin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to explain (1) the formulation of strategic management and (2) the implementation of strategic management in teaching Arabic at the Mumtaza Islamic Boarding School. This research is qualitative. In collecting data, researchers used 3 methods, namely the document method, interview method, and observation method. According to Miles and Huberman, the data analysis used is data induction, presentation, inference, and verification. From this research, it was found that the Mumtaza Islamic Boarding School: (1) has specifically formulated its strategy so that its organization operates effectively, productively and efficiently; (2) implements systematic and detailed operational strategies in Arabic Language Teaching, including (a) making the teaching of Arabic and the Koran a single unit in education; (b) cut the number of subjects to 8, (c) allocate more class hours; (d) teach Arabic based on language competency, (e) use activity-based teaching methods.